Jeffrey C. Kinley, ed., After Mao, Chinese Literature and Society, 1978-1981, Cambridge, Mass., The Council on East Asian Studies, Harvard University Press, 1985, 345 pp. - Connelly, Marisela (Estudios de Asia y África, 1987)
-